Osteochondroma of the Distal Tibia Leading to Deformity and Stress Fracture of the Fibula - A Case Report - Singh, Chander Mohan; Thapa Magar, Mohit; Sud, Ajay Deep (Medical Journal of Shree Birendra Hospital, 2021)
Osteochondromas seldom arise from the interosseous border of the distal tibia and may progress to involve the distal fibula. We present the case of a 14-year-old teenager with a stress fracture of the distal fibula, secondary to an osteochondroma arising from the distal tibia. Early excision of this deforming distal tibial osteochondroma was necessary in order to avoid a progressive deformity which would affect the biomechanics of the ankle joint resulting in gait disturbances.